Analysis of the Application of Marketing Mix to Increase Sales at Store Dikromoshop Bandar Lampung - Novita, Atika; Rinova, Dora (International Journal of Economics (IJEC), 2025)
When running a business, a company implements a marketing strategy to reach a predetermined target and optimize sales results. One marketing strategy implemented by Dikromoshop is a marketing mix strategy consisting of, product, price, place, promotion, people, process, and physical evidence. This study analyses the extent of the marketing mix strategy applied by Dikromoshop to increase sales and the factors that play a role in supporting or inhibiting the application of marketing mix strategies to increase sales at Dikromoshop stores. This research uses a qualitative descriptive approach by collecting data directly through observation, interviews, and documentation with the owner, employees, and consumers of Dikromoshop Bandar Lampung. The results of this study indicate that the application of the marketing mix Strategy by Dikromoshop in an effort to increase sales volume has been carried out to the maximum in accordance with the principles of relevant theory, which proved to have a crucial role in increasing sales volume. The supporting factors are quality products at affordable prices, products that are not market, social media promotions, and discounts such as flash sales given on twin dates. Then, the inhibiting factors are competition and lack of innovation in clothing products, followed by the payment process, which only supports payments via cash and transfers to one bank.